'Then you can ride the scooter to run away!' Gender positioning of marriage-migrants in adult Mandarin education in Taiwan. Issue 6 (18th August 2018) - Lin, Shumin
ABSTRACT: This study aimed to explore how gender restructuring might interact with immigrant second language (L2) learning in the new trends of feminized marriage migration in Asia, using Mandarin-language education in Taiwan as a case study. Drawing on positioning theory to analyze classroom discourse in a Mandarin-language class for marriage-migrants, this paper shows how the societal gendered expectations of marriage-migrants are concretely manifested and discursively negotiated in the classroom. As the teacher interactively positioned students as runaways, potential transgressors of chaste womanhood, and unfit mothers, the focal student reflectively positioned herself as an autonomous woman, capable mother, avid language learner, and multilingual speaker. By focusing on the dynamic negotiations of gender positionings in the language classroom for marriage-migrants in Asia, this study extends current research on immigrant L2 education to examine the nexus of globalization, transnational marriage migration, gender, and adult immigrant education.